Microfluidics revealing formation mechanism of intermetallic nanocrystals. (April 2020) - Zhang, Dongtang; Wang, Yanan; Deng, Jiguang; Wang, Xiayan; Guo, Guangsheng
Abstract: Insightful understanding of the reaction mechanisms that control both growth and phase formation is one of the most challenging issues in ordered intermetallic catalysts. In this study, we developed a microfluidic system with a millisecond time resolution for the synthesis of PtSn intermetallic nanocrystals, with which the complex formation mechanism of intermetallic phase was enabled to investigate. The result revealed that the formation of PtSn nanocrystals occurs in four stages: increasing monomer, burst nucleation of monomers and intermetallic phase formation, growth and particle attachment, and sintering stage. The products in the range of milliseconds to seconds can be obtained by different lengths of reaction microchannels. This setup allowed control of the phases of the PtSn nanocrystal growth and thereby tuned the catalytic performance of the ethanol oxidation reaction. Such an understanding of the growth of pathways is significant for the design of ordered intermetallic nanocatalysts. Graphical abstract: We developed a microfluidic approach to synthesize intermetallic nanocrystals and reveal the formation mechanism by millisecond time resolution. Image 1 Highlights: We developed a microfluidic strategy to synthesize intermetallic nanocrystals with a millisecond time resolution. Proposed intermetallic phase formation mechanism: increasing monomer, burst nucleation, growth and attachment, sintering. This microfluidic system allowed control of the phases and architectures of the PtSn nanocrystal.